Simulasi Pemerkiraan Parameter Sifat Fisikawi Bahan Makanan dengan Metode Penjejak Parameter - B. Rahardjo (agriTECH, 1994)
Simulation of the parameter tracking method was used to estimate the physical parameters of food material. The input-output relationships of the materials were based on known mathematical models. Three mathematical models of the food properties were studied: the Kelvin model of linear viscoetastic material, the power law of non Newtonain liquid, and the impact model of a non linear viscoelastic spherical object. The results indicated that the parameter tracking method can determine the parameters of the models correctly. However the speed of the estimation depends on the models. The estimation of the parameters of the linear model converged Faster than that of non linear models.